A framework for implementing lean manufacturing system in small and medium enterprises - Wanitwattanakosol J. (2014)
In this paper, a conceptual framework to apply many techniques for implementing lean in the high-variety low-volume (HVLV) environment is presented. Lean production has increasingly being implemented as a potential solution for many organizations. Anyway, the lean formula is applicable directly only to the make-to-stock business, but the make-to-order (MTO) product environment has to adapt lean manufacturing principle. The method of this paper has a twophase quantitative framework to transform small and medium enterprises (SMEs) to be lean. Phase 1 has three interrelated components: (1) re-engineering an organization by using the power of computer simulation combined with business process. (2) Value stream mapping (VSM) is used to create a map of both value and waste in a given process. This tool has also a main drawback for job shop facility because many value streams are composed of hundreds of industrial parts and products. (3) Integrative supplier relationship is one of the most critical factors to maintain an advantage in the increasing levels of competition. Phase 2 performs a just in time production schedule by using ant colony optimization technique combines with a simulation tool. The aims of this paper are to develop a suitable lean manufacturing system for SMEs and to study the performance of the system for improving effectiveness. The result shows how to combine lean concept with simulation optimization, the step of this framework to obtain the optimization solution. © (2012) Trans Tech Publications, Switzerland.